2007
DOI: 10.1093/toxsci/kfm102
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and Inflammation in the Nasal Airways of Mice Exposed to the Macrocyclic Trichothecene Mycotoxin Roridin A: Kinetics and Potentiation by Bacterial Lipopolysaccharide Coexposure

Abstract: Macrocyclic trichothecene mycotoxins produced by indoor air molds potentially contribute to symptoms associated with damp building illnesses. The purpose of this investigation was to determine (1) the kinetics of nasal inflammation and neurotoxicity after a single intranasal instillation of roridin A (RA), a representative macrocyclic trichothecene; and (2) the capacity of lipopolysaccharide (LPS) to modulate RA's effects. C57Bl/6 female mice were intranasally instilled once with 50 mul of RA (500 mug/kg body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 64 publications
10
59
1
Order By: Relevance
“…In accordance to our OTA data, fumonisin B 1 (FB 1 ) [31] as well as trichothecene mycotoxins [15] have been demonstrated to induce apoptosis in cultured neurons.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance to our OTA data, fumonisin B 1 (FB 1 ) [31] as well as trichothecene mycotoxins [15] have been demonstrated to induce apoptosis in cultured neurons.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the OE lining the dorsal medial meatus of the mouse nasal cavity had no microscopic evidence of SG-induced injury (Islam et al 2006). This same distribution of injury was also observed in mice following exposure to another macrocyclic trichothecene mycotoxin, roridin-A (Islam et al 2007). One possible explanation for this interspecies variation is the difference in airflow patterns through the nasal airways of rodents and nonhuman primates.…”
Section: Discussionsupporting
confidence: 66%
“…Our observations demonstrate that the nasal airways of rhesus macaques, an animal model whose upper airways are structurally and functionally similar to those of humans, are vulnerable to injury induced by SG, and raise new questions about the potential hazards associated with exposure to S. chartarum in water-damaged environments. Olfactory mucosal injury has been previously described in the nasal airways of laboratory mice following intranasal exposure to low doses of SG, as well as other macrocyclic trichothecene mycotoxins (Corps et al 2010;Islam et al 2007Islam et al , 2006. In the present study, we used a comparable, low dose of SG (1 mg per nasal passage) to determine whether the olfactory mucosa of rhesus monkeys, a model for the nasal airways of people, exhibits similar vulnerability.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that single, intranasal instillations of RA cause OE atrophy, loss of OSNs, and OB atrophy (Islam et al 2007). Single instillations of RA also resulted in neutrophil infiltration in the affected OE and associated lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that mice instilled once intranasally with a relatively low amount (250 ng) of the macrocyclic trichothecene satratoxin G (SG) develop rapid and dramatic loss of olfactory sensory neurons (OSNs), through apoptosis, in both the nose and brain (Islam, Harkema, and Pestka 2006). In a subsequent study, it was found that roridin A (RA), a macrocyclic trichothecene with a similar chemical structure, similarly induced rapid apoptosis and marked loss of OSNs in the nasal airways and the olfactory bulb (OB) of mice after a single intranasal instillation (Islam et al 2007).…”
Section: Introductionmentioning
confidence: 99%